PENINGKATAN KADAR BIOETANOL DARI KULIT NANAS MENGGUNAKAN ZEOLIT ALAM DAN BATU KAPUR - Harimbi Setyawati, Nanik Astuti Rahman (Jurnal Teknik Kimia, 2012)
The use of zeolite and limestone as an adsorbent in an attempt to improve the purity of bioethanol from pineapple rinds. Sugar content contained in pineapple rinds is only about 8% so it is still very little bioethanol produced. Of the fermentation process of pineapple rinds  juice with Saccaromyces cereviceae  and ethanol distillation process obtained the highest levels of only 3.9%. With the distillation repeated for three times the concentration of ethanol does not increase, it is necessary for an alternative method is to purification other adsorption processes. Adsorbents used in this study is the natural zeolite and limestone obtained from the southern city of Malang. The results showed that the ethanol content increased to once passed through the zeolite adsorbent and limestone. Activation treatment, both physically and chemically strongly influences the adsorption process. Key words : adsorption, bioethanol, lime stone, zeolite